2018
DOI: 10.1080/1331677x.2018.1543056
|View full text |Cite
|
Sign up to set email alerts
|

Corporation effective tax rates and company size: evidence from Germany

Abstract: We investigate the relationship between the effective tax rate (E.T.R.) and company size in Germany to test tax planning-political power versus political cost theories. In contrast to most studies in this field, which use linear approximations, this paper uses a quantile regression approach. We use data from Compustat, corresponding to non-financial listed companies during 1992-2009. The results indicate a nonlinear relation, with a positive sign for the first quantiles and a negative one in the last part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
2
17
0
3
Order By: Relevance
“…Thus, the related research hypotheses (H 2 and H 3 ) are confirmed. The result concerning the first variable is in line with Delgado et al (2018), Irianto et al (2017), Liu and Cao (2007). Most previous studies (Gupta and Newberry, 1997;Richardson and Lanis, 2007) that did not directly control for the effect of tax benefits envisaged to incentivise the investment in tangible fixed assets initially hypothesised and later found that a statistically significant and negative association exists between the incidence of tangible fixed assets and the ETR.…”
Section: Parametersupporting
confidence: 76%
“…Thus, the related research hypotheses (H 2 and H 3 ) are confirmed. The result concerning the first variable is in line with Delgado et al (2018), Irianto et al (2017), Liu and Cao (2007). Most previous studies (Gupta and Newberry, 1997;Richardson and Lanis, 2007) that did not directly control for the effect of tax benefits envisaged to incentivise the investment in tangible fixed assets initially hypothesised and later found that a statistically significant and negative association exists between the incidence of tangible fixed assets and the ETR.…”
Section: Parametersupporting
confidence: 76%
“…needs to be assumed due to a semiparametric nature of the quantile regression method (see e.g. Delgado et al, 2018;Zivkov et al, 2014). In a two-asset QR framework, where y is linearly dependent on x, then s th conditional quantile function of y is given in the following way:…”
Section: Quantile Regression Approachmentioning
confidence: 99%
“…This measure allows us to capture some of the fiscal incentives that firms are able to use according to the Ecuadorian tax structure that could reduce the firm's tax obligation. While this measure depends on a specific country's accounting rules and regulations, it can be used to compare ETRs across countries with differing statutory taxes and rates and tax bases (Delgado et al, 2018).…”
Section: Empirical Frameworkmentioning
confidence: 99%